The Effects of Berberis vulgaris Fruit Extract on Serum Lipoproteins, apoB, apoA-I, Homocysteine, Glycemic Control and Total Antioxidant Capacity in Type 2 Diabetic Patients - Shidfar, Farzad (Shaheed Beheshti University of Medical Sciences, 2012)
Type 2 diabetes is a well-known endocrine and metabolic disorder which has reached epidemic proportions worldwide and represents a serious public health concern. Hyperglycemia and dyslipidemia are two major abnormalities which are major cardiovascular risk factors. Berberine is a major alkaloid in Berberis vulgaris fruit extract (BVFE) which have important role in regulation of serum glucose and fat metabolism in-vivo and in-vitro but its role in type 2 diabetes have not been extensively examined. The aim of this study was the effect of BVFE on serum lipoproteins, apoB, apoA-I, homocysteine, glycemic control and total antioxidant capacity in type 2 diabetic patients. In a double-blind randomised clinical trial, 31 diabetic patients were randomly assigned to 3 g/d BVFE or placebo for 3 months. Serum glucose, lipoproteins, apoB, apoA-I, insulin, homocysteine and HbA1c were measured at the baseline and also at the end of the 3(rd) month. At the beginning and end of 1(st), 2(nd) and 3(rd) months, a 24-h dietary recall questionnaire about each patients was completed. Data were analyzed by SPSS version 16. There were significant decreases in serum TG, TC, LDL-c, apo B, glucose, and insulin and also a significant increase in TAC at the end of the study in BVFE group compared to the control group (p = 0.001, p = 0.001, p = 0.001, p = 0.001, p = 0.002, p = 0.01 and p = 0.0001 respectively). There were significant differences in serum TG (p = 0.0001), TC (p = 0.001), LDL-c (p = 0.001), apoB (p = 0.001), glucose (p = 0.002), insulin (p = 0.01), TAC (p = 0.005), and insulin resistance (p = 0.01) between the two groups at the end of the study; but homocysteine, HbA(1c) and HDL-c showed no significant changes between the two groups at the end of study. The intake of 3 g/d BVFE for 3 months may have benefical effects on lipoproteins, apoproteins, glycemic control and TAC in type 2 diabetic patients.